A novel heterozygous mutation of ANKRD11 causes KBG syndrome in a preterm neonate: a case report and literature review - Gao, Jie; Wang, Ruiqin; Pan, Zhen; Hu, Ruolan; Jiang, Mingyan; Li, Jinrong (Frontiers in Pediatrics, 2025)
The KBG syndrome (KBGS) affects several systems caused by the mutation of the ANKRD11 gene. The main manifestations of KGBS included hearing loss, feeding difficulties, craniofacial abnormalities, tooth deformity, and developmental delay (delayed overall development, convulsions, and intellectual abnormalities). Only 10%–26% of patients with KBG syndrome have congenital heart disease, including atrial and ventricular septal defects. Here, we report a case of KBG syndrome in a preterm newborn with low birth weight, a huge ventricular septal defect, and a congenital chylothorax. Whole-exome sequencing detected an ANKRD11 gene mutation in the infant. The finding expands the understanding of the clinical and genetic phenotype. The multidisciplinary consultation of the complex KGB syndrome including interventional occlusion, nutritional management, and rehabilitation training can improve the prognosis and outcome.